A Qualitative Study: Quality of Life in Patient with Post Stroke Attack - Dewi , Ni Luh Putu Thrisna; Suhartini Ismail (Basic and Applied Nursing Research Journal, 2020)
Background: Post stroke attack, usually patient will face many diseases complaint physically, psychologically and emotionally. This affects the ability of patient to do the activity in daily lives (ADL) even it causes the decline of the quality of life post stroke attack. Purpose: Identifying the patient’s understanding regarding the quality of life deeply which they have post stroke attack. Method: the method used is qualitative study. Data collection using interview guidelines that arranged by the researcher as an open ended question and held with in-depth interview semi structure. Result: The result of this research identifying 4 main themes i.e. (1) Hampered in doing daily activities, (2) Changes the meaning of life due to physical limitations, (3) Psychological response due to loss and limitations of social relations, (4) Stroke patients require a health care professional.The result of this research shows post stroke attack patient dominant suffer physical disorders and physiology so it has an impact to the social relation in their environment. Patient’s quality of life is affected by sequelae they have. Conclusion: Patient feels limited in doing daily activities independently post stroke attack. Patient really need professional service to fix the quality of life. Recommendation: The health service needs to be improved according to the standard to prevent the sequelae to increase to help fix patient’s quality of life.